Pathways of memory CD8+ T-cell development. - Bannard, O; Kraman, M; Fearon, D (2009)
CD8(+) T-cell responses must have at least two components, a replicative cell type that proliferates in the secondary lymphoid tissue and that is responsible for clonal expansion, and cytotoxic cells with effector functions that mediate the resolution of the infection in the peripheral tissues. To confer memory, the response must also generate replication-competent T cells that persist in the absence of antigen after the primary infection is cleared. The current models of memory differentiation differ in regards to whether or not memory CD8(+) T cells acquire effector functions during their development. In this review we discuss the existing models for memory development and the consequences that the recent finding that memory CD8(+) T cells may express granzyme B during their development has for them. We propose that memory CD8(+) T cells represent a self-renewing population of T cells that may acquire effector functions but that do not lose the naïve-like attributes of lymphoid homing, antigen-independent persistence or the capacity for self-renewal.